2016
DOI: 10.18632/oncotarget.9014
|View full text |Cite
|
Sign up to set email alerts
|

Significance of microRNA-related variants in susceptibility to recurrence of oropharyngeal cancer patients after definitive radiotherapy

Abstract: Common single nucleotide polymorphisms (SNPs) in miRNAs may affect miRNA functions and their target expression and thus may affect biological activities and cancer etiology as well as prognosis. Thus, we determined whether the 9 SNPs in microRNAs modify the risk of recurrence of squamous cell carcinoma of the oropharynx (SCCOP) in a cohort of 1008 patients. The log-rank test and multivariate Cox models were used to evaluate the associations. We found that the SNPs in the miRNA146, miRNA196, and Gemin3 were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…MiRNAs are responsive to various cellular stressors and are key players in many diseases including cancer [ 8 , 9 ]. Studies have shown that miRNAs may affect cancer development and the regulation of the immune/inflammation or cell death responses as well as may be used in early detection, diagnosis and prognosis of different diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are responsive to various cellular stressors and are key players in many diseases including cancer [ 8 , 9 ]. Studies have shown that miRNAs may affect cancer development and the regulation of the immune/inflammation or cell death responses as well as may be used in early detection, diagnosis and prognosis of different diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms of miRNAs have been identified to affect miRNA processing and alter miRNA expression (50). Some researchers have shown that miR-492 rs2289030 G > C was associated with various cancers (50, 62, 67, 86). Lee et al found CRC patients carried CG and GG genotype demonstrated worse RFS when compared with CC genotype.…”
Section: Discussionmentioning
confidence: 99%
“…93 The variant A allele of SNV Gemin3 (DDX20) rs197388 was associated with altering the process of the mature miRNAs for translational repression compared to the wild-type T allele, and thus with recurrence of OPSCC. 94 Moreover, miR-146 rs2910164 variant C and miR-196 rs11614913 wild-type C alleles were associated with OPSCC poor prognosis, compared to the wild-type G and variant T alleles, respectively, although the exactly mechanism by which these variants may influence OPSCC prognosis was not clear. 94 The variant alleles of SNVs miR-149 rs2292832 T and miR-499 rs3746444 C were associated with poor prognosis compared to the wild-type A and T alleles, respectively, although the exactly mechanism by which these variants may influence OSCC, HPSCC and LSCC prognosis was not clear.…”
Section: Snvs In Mirnas-coding Sequences and Mirnas Processing Genementioning
confidence: 99%
“…94 Moreover, miR-146 rs2910164 variant C and miR-196 rs11614913 wild-type C alleles were associated with OPSCC poor prognosis, compared to the wild-type G and variant T alleles, respectively, although the exactly mechanism by which these variants may influence OPSCC prognosis was not clear. 94 The variant alleles of SNVs miR-149 rs2292832 T and miR-499 rs3746444 C were associated with poor prognosis compared to the wild-type A and T alleles, respectively, although the exactly mechanism by which these variants may influence OSCC, HPSCC and LSCC prognosis was not clear. 95 Also, MIR100HG, a long non-coding RNA from which miR-100 originate, rs1816158 variant C allele was associated with poor prognosis in OSCC, pharyngeal SCC and LSCC, compared to the wild-type A allele, possibly due to the miR-100 expression increasing, associated with tumor invasion and migration.…”
Section: Snvs In Mirnas-coding Sequences and Mirnas Processing Genementioning
confidence: 99%
See 1 more Smart Citation